For freedom and independance of Poland : documents : july 1947 - May 1948 = W obronie wolności i niepodleglości rzeczypospolitej polskiej : dokumenty : Lipiec 1947 - Maj 1948. (London, 1948)
Bibliotheek Camille Huysmans
Engels
Pools
Brochure
Keywords: onafhankelijkheid; Polen